Association between interpersonal relations and anxiety, depression symptoms, and suicidal ideation among middle school students - Meixin Zheng; Xiaoyan Guo; Zhiyan Chen; Jing Deng; Mi Hu (Frontiers in Public Health, 2023)
ObjectiveThis study aimed to explore the relationship between different types of interpersonal relationships and anxiety symptoms, depressive symptoms, and suicidal ideation and discusses the impact of different grades among middle school students.MethodsThe Patient Health Questionnaire Depression Scale, the Chinese version of the Generalized Anxiety Scale, suicidal ideation questions, and interpersonal relations items were used to measure the depression symptoms, anxiety symptoms, suicidal ideation, and interpersonal relations of the participants. The variables of anxiety symptoms, depressive symptoms, suicidal ideation, and interpersonal relations were screened using the Chi-square test and principal component analysis. AMOS17.0 constructs the path of the association between interpersonal relations and depressive symptoms, anxiety symptoms, and suicidal ideation.ResultsThe mother-child relationship had direct impacts of −0.06, −0.07, and −0.06 on anxiety symptoms, depressive symptoms, and suicidal ideation. On anxiety symptoms, depressive symptoms, and suicidal ideation, the direct impacts of the father-child relationship were −0.09, −0.03, and −0.08. Moreover, the direct effects of peer relationships on depressive symptoms were −0.04, whereas the direct impact of teacher-student relationships on anxiety and depressive symptoms were −0.10 and −0.09. Further pathway analysis based on grade level showed that in the junior high school model, the direct effect of the mother-child relationship on anxiety and depressive symptoms was −0.18 and −0.16. The direct impact of the father-child relationship on depressive symptoms and suicidal ideation was −0.08 and 0.09. The direct effect of peer relationships on depressive symptoms was −0.08, and the direct impact of the teacher-student relationship on anxiety symptoms was −0.06. In the high school model, the direct effect of the mother-child relationship on suicidal ideation was −0.07, while the direct impact of the father-child relationship on anxiety, depression, and suicidal ideation was −0.10, −0.07, and −0.12, respectively. In addition, the direct effects of peer relationships on anxiety and depression were −0.06 and −0.05, and the direct impact of teacher-student relationships on anxiety and depression was −0.10 and −0.11.ConclusionThe father-child relationship affects suicidal ideation and depression the most, followed by the mother-child relationship, the teacher-student interaction, and the peer relationship. The teacher-student relationship influences anxiety symptoms the most, followed by the father-child and mother-child relationships. The association between interpersonal interactions and anxiety, depressive symptoms, and suicidal ideation varied significantly across grade levels.